The Old Testament Editor of the First Published Greek New Testament: Johannes Oecolampadius (1482–1531) - Fisher, Jeff (Journal of Early Modern Christianity, 2018)
Following its publication in March 1516, Erasmus’s Novum Instrumentum became one of the most significant texts for the Reformation. A less explored element of the development of this first published Greek New Testament is the role of the Old Testament editor, Johannes Oecolampadius (1482-1531). This study focuses on the contributions of Oecolampadius with particular attention given to the Annotations on Romans. By looking through the lens of the remarks in the Novum Instrumentum regarding the Hebrew language and the Old Testament, and comparing them with the lectures by Martin Luther on Romans that he finished with the use of this newly available resource, the influence Oecolampadius had on Luther before his famous action in October 1517 becomes more apparent. Notably, then we can see the resulting influence of Luther on Oecolampadius to embrace the newly forming evangelical teaching and eventually become the leading reformer in Basel.